Choices, challenges and the power of integration: regionalism and confederation in the East African community - a hypothesis generating study - Schollij, Rochella (Department of Political Studies, 2014)
The focus of this hypothesis generating study is to open new areas of research within the study of regions and regionalization in the East African Community and beyond. By using a null hypothesis that encapsulates the reigning attitudes within models of economic integration, this paper exposes many of the issues that are left unaddressed in models of regionalization driven by economics. In order to accurately assess the relevant issues, the paper is divided into three statements that underpin the null hypothesis;; each statement focuses on an aspect of economic integration and explores the effect that it has on member states in the regionalization process. Through this evaluation the three statements and their respective effects are linked to each other and to the null hypothesis to form a web that supports the alternative hypothesis. As a result, it offers paths for future research to improve on regional theory. The aim of this paper is to uncover the failings of an "economics-first" approach. As a result it includes many of the prevalent debates within regional theory, including the issues of Eurocentrism and the false dichotomy between politics and economics within integration. In addition, it includes ideas around nationalism, identity and the role of the state and citizenry within regions. It also introduces the idea of a confederation as a possible alternative to a federation with a monetary union. Through assessing the work of David Mitrany and Ernst B. Haas, this paper tracks the failings within the foundations of regional integration theory through to New Regionalism and the work of Bela Balassa. This forms the basis for attacking the null hypothesis. The issues raised are pulled through the paper, attaching the theoretical flaws to their practical consequences. By applying these findings to the case study of the East African Community, this paper paints a compelling argument as to why regions in Africa should reassess their methods and goals within the regionalization process. Developing states in particular must be cognizant of the effect of neglecting their domestic responsibilities. In addition, due to the nature of this study the findings can be transposed to the European context. This is particularly pertinent given the political, economic and social issues the EU currently faces in the wake of the 2008 recession. The results suggest that regional integration programmes need to incorporate a political approach within integration models. Economic integration can only be sustainable and beneficial where agreements are underpinned by political will and where the state is an active and empowered participant in the integration process. By alienating the state the regionalization process sabotages itself. The solution must therefore include a reassessment of the intentions of regional theory with the aim of re-linking the goals of member states to the methods and outcomes they choose. This empowers the participants in a regionalization programme and enhances the long-term commitment of states to a regional cause.